Modeling the zebrafish gut microbiome’s resistance and sensitivity to climate change and parasite infection - Sieler, Michael J.; Al-Samarrie, Colleen E.; Kasschau, Kristin D.; Kent, Mike L.; Sharpton, Thomas J. (Frontiers in Microbiomes, 2025)
IntroductionAs climate change increases global water temperatures, ecologists expect intestinal helminth infection ranges to expand and increase the health burden on aquatic organisms. However, the gut microbiome can interact with these parasites to influence infection outcomes, raising the possibility that its response to increasing temperatures may help buffer against increased infection burden or worsen infection outcomes (e.g., inflammatory bowel disease). To evaluate this hypothesis, we sought to determine if the microbiome is resistant or resilient to the stressors of increased water temperature, helminth exposure, and their combination, and whether this variation linked to infection outcomes.MethodsWe leveraged the zebrafish (Danio rerio) model organism to measure how these variables relate to the temporal dynamics of the gut microbiome. In particular, we exposed adult zebrafish to Pseudocapillaria tomentosa, parasitic capillarid with a direct life cycle, across three different water temperatures (28°C, 32°C, 35°C), and analyzed fecal microbiome samples at five time points across 42 days.ResultsOur findings show that parasite exposure and water temperature independently alter gut-microbiome diversity. Moreover, water temperature moderates the association between parasite infection and the gut microbiome. Consistent with this observation, yet counter to prevailing expectations, we find that increasing water temperature reduces P. tomentosa infection worm development and overall abundance in zebrafish. The decline in worm burden at 35°C may be due to either direct thermal inhibition of P. tomentosa development or temperature-mediated interactions with the host microbiome and immune response.DiscussionOverall, our results indicate that water temperature alters the contextual landscape of the gut microbiome and shapes its response to an intestinal parasite in zebrafish. To our knowledge, this represents the first report of elevated temperature constraining nematode development in a fish host, underscoring that climate change may impose unanticipated, context-dependent impacts on vertebrate gut microbiomes and health outcomes.